ANALISA PENETAPAN HARGA POKOK PRODUKSI SECARA CEPAT DAN TEPAT DENGAN MENGGUNAKAN METODE FULL COSTING - RUNDUPADANG, HELBA (Jurnal Unicorn ADPERTISI, 2022)
The purpose of this study is to analyze the determination of the cost of producing water using the Full Costing method quickly and accurately as the basis for determining the selling price for each cubic meter at the Regional Public Company (PERUMDA) Drinking Water in North Toraja Regency. The type of research used is descriptive quantitative and qualitative by interviewing PERUMDA Water Supply in North Toraja Regency and processing data from the 2021 financial report PERUMDA Water Supply in North Toraja Regency using the full costing method. The results show that the determination of the Cost of Production in 2021 is using the full costing method is already a fast and accurate way because in 2021 PERUMDA Water Supply in North Toraja Regency will experience a profit, with the selling price for each cubic meter greater than the cost of production